Estimasi Faktor Yang Mempengaruhi Biaya Usahatani Padi Di Kecamatan Turatea Kabupaten Jeneponto - Andi Alifa, Andi Amran Asriadi; Husain, Nailah (Jurnal AGRIBIS, 2025)
The purpose of the study was to determine the factors that affect the cost of rice farming in Turatea District, Jeneponto Regency. This study uses a quantitative approach. This research uses a quantitative approach. This research uses primary and secondary data. The data analysis method of this work uses multiple linear regression models using SPSS version 25. Tests were carried out with classical assumption tests such as normality test, autocorrelation test, heteroscedasticity test, multicollinearity test, F-test. (simultaneous) and t-test (partial). The results of this study indicate that the factors that have a significant positive effect on the cost of rice farming include fertilizer costs (X1), and labor costs (X2) to farming costs. Factors that do not have a significant impact on farming costs such as seed costs (X3), pesticide costs (X4), and rice production (X5). In rice production if the production conditions are well utilized, rice production will be better, meaning that the output part of production is greater than the input part of the output, that is, the income from the costs incurred will be greater so that income can also increase.